Manejo eficiente de desechos peligrosos hospitalarios generados en el centro de salud Velasco Ibarra tipo C - Poggio Víctor, Kennia Elizabeth (My University, 2019)
The present work was developed with the main objective of designing a manual of processes for the efficient management of hazardous waste generated in the health center Velasco Ibarra Type C, in order to efficiently manage such waste. The research was of a qualitative nature, for them we proceeded to the revision of texts, scientific articles, doctoral or magisterial works and regulations related to the objective of the research. The manual allowed a detailed description of the aspects to be taken into account for the proper management and development of the internal management of hazardous wastes, as well as the categorization of the different types of hazardous waste for an efficient treatment, contains the necessary technical elements for the optimization of resources and the continuous improvement of the management of hospital hazardous waste, since it establishes the appropriate technological resources for the different types of treatment of hazardous waste to be treated, the manual was extended to all persons who in the development of their activities generate hazardous waste in the health center.
El presente trabajo fue elaborado con el objetivo principal de diseñar un manual de procesos para el manejo eficiente de desechos peligrosos generados en el centro de salud Velasco Ibarra Tipo C, con el fin de gestionar eficientemente dichos residuos. La investigación fue de carácter cualitativa tuvo, para ellos se procedió a la revisión de textos, artículos científicos, trabajos doctorales o magistrales y normativas relacionadas al objetivo de la investigación. El manual permitió una descripción detallada de los aspectos a tener en cuenta para el adecuado manejo y el desarrollo de la gestión interna de los desechos peligrosos, así como la categorización de los diferentes tipos de desechos peligrosos para un tratamiento eficientes, contiene los elementos técnicos necesarios para la optimización de los recursos y el mejoramiento continuo de la gestión de los desechos peligrosos hospitalarios ya que establece los recursos tecnológicos adecuados para los diferentes tipos de tratamiento de desechos peligrosos a tratar, el manual se extendió a todas las personas que en el desarrollo de sus actividades generen residuos peligrosos en el centro de salud.
Keywords: MANEJO; DESECHO; PELIGROSO; HOSPITALARIO